(untitled) (Revista científica Olimpia, 2025)
In an analysis of the content of the general preparation program for soccer players and by applying the observation method in training, it was possible to corroborate the negative consequences that traditional training generates in players due to its nature. Taking this need into account, this research is developed with the objective of developing the technical-tactical offensive thinking of the soccer players of the Bayamo team category 11-12. The study addresses very important and necessary topics to understand this complex sport. At the same time, a proposal of exercises is presented, which gives coaches a different way of training and developing athletes, as long as their implementation is guided by training methodologies with ideas and concepts different from the traditional one, which brings as consequences alternative training.